Java foundation classes in a nutshell : a desktop quick reference - Flanagan, David (Java series (O'Reilly & Associates), 1999)
Intended for Java programmers writing applications or applets involving graphics or graphical user interfaces and is a companion to the book entitled, "Java in a Nutshell, 3rd ed."